2022
DOI: 10.3390/met12040661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micro-Structural Dispersity of SiMo Ductile Iron on High Temperature Performance during Static Oxidation

Abstract: High silicon and molybdenum (SiMo) ductile iron is commonly used for car exhaust systems, and its micro-structural dispersity depends on intrinsic parameters, which include alloy composition and inoculation efficiency, as well as extrinsic factors, such as casting wall thickness and molding material, which define cooling rate during solidification. Micro-structural dispersity is referred to as the degree of heterogeneity of sizes of structural constituencies within the microstructure. A variation in the micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The control of heterogeneous nucleation in combination with alloying by Si, Al and Mo were used to improve the high-temperature performance of SGI [18][19][20][21][22][23][24]. Additional melt treatment was used for the development of a dual graphite structure with controlled zones from the flake and spherical graphite shapes in one casting [25,26].…”
Section: Control Solidification Kinetics For Self-healing Microporosi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The control of heterogeneous nucleation in combination with alloying by Si, Al and Mo were used to improve the high-temperature performance of SGI [18][19][20][21][22][23][24]. Additional melt treatment was used for the development of a dual graphite structure with controlled zones from the flake and spherical graphite shapes in one casting [25,26].…”
Section: Control Solidification Kinetics For Self-healing Microporosi...mentioning
confidence: 99%
“…However, the following instabilities of freely growing interfaces produce morphological shape evolution. The factors that lead to shape instability include: (i) surface energy of a curved interface, (ii) atom attachment kinetics, (iii) trapping solute elements, (iv) mass transport of alloying elements, and finally, (v) possible The control of heterogeneous nucleation in combination with alloying by Si, Al and Mo were used to improve the high-temperature performance of SGI [18][19][20][21][22][23][24]. Additional melt treatment was used for the development of a dual graphite structure with controlled zones from the flake and spherical graphite shapes in one casting [25,26].…”
Section: Effect Of Heterogeneous Nucleation On Shape Of Primary Facet...mentioning
confidence: 99%
“…In addition, silicon enhances high temperature oxidation resistance by forming a silicon-rich oxide layer. The high-temperature oxidation behavior of SiMo nodular cast iron has been studied in dry air, wet air (air + 10% H 2 O), and exhaust gas environments at elevated temperatures (650 to 1050 • C) by many researchers [14][15][16][17][18][19][20][21]. These studies showed that when SiMo cast iron was exposed to high temperatures in the presence of air and exhaust gases (synthetic diesel and gasoline), it formed a multilayered oxide scale.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the silica film was much more favorable at 800 • C than at 700 • C [26]. However, Lekakh et al [19,27] showed that the protective and continuous amorphous silica layer obtained in the SiMo cast iron was limited at 700 • C since the oxygen permeability of the amorphous silica layer increased above 750 • C and promoted a decarburization reaction near the interface. The high pressure of CO gas from decarburization caused deformation of the metal matrix, which led to delamination in the brittle silica oxide layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation